Carbon and Nutrient Transfer via Above and Belowground Litter in Forests (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint highlights the ecological importance of forest litter in nutrient cycling, the sequestration of soil carbon, and the formation of soil organic matter. The results presented would be of great importance for the improvement of forest services against the background of the global climate change scenario.